Squamous Cell Head and Neck Cancer Recent Clinical Progress and Prospects for the Future - Adelstein, David J.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2005)
Although squamous cell head and neck cancer is not the most common cancer in the United States, it is an important and disabling malignancy that-through the advances recently achieved by multiple medical disciplines-serves as a model of multimodality solid tumor management. In Squamous Cell Head and Neck Cancer: Recent Clinical Progress and Prospects for the Future, leading expert physicians and investigators from around the world review the state of the art in the management of squamous cell head and neck cancer, with emphasis on coordinating different treatment modalities. The authors address several surgical issues, including laser-based surgery, larynx preservation approaches, salvage surgery, and neck management after non-operative treatment. They also discuss definitive radiation for larynx cancer, brachytherapy, altered fractionation radiation, intensity modulated radiation therapy, and the importance of tumor hypoxia, as well as the role of chemotherapy in sequential, concurrent, and adjuvant multimodality treatment schedules. Other topics of special interest include targeted and gene therapies, multimodality management of nasopharyngeal cancer, chemoprevention, toxicity modification, quality of life outcomes, symptom palliation, and epidemiology. Comprehensive and authoritative, Squamous Cell Head and Neck Cancer: Recent Clinical Progress and Prospects for the Future offers head and surgeons, radiation oncologists, and medical oncologists an interdisciplinary review of recent successes on multiple fronts in the treatment of this disease, as well as a blueprint for future investigation.
Head and Neck Squamous Cell Cancers in the Nonsmoker-Nondrinker -- Laryngeal Preservation Surgery -- Laser Surgery for Head and Neck Cancer -- The Evolving Role of Neck Dissection in the Era of Organ Preservation Therapy for Head and Neck Squamous Cell Carcinoma -- Salvage Surgery After Chemoradiation Therapy -- T3–T4 Squamous Cell Carcinoma of the Larynx Treated With Radiation Therapy Alone or Combined With Adjuvant Chemotherapy -- Role of Brachytherapy in Treatment of Head and Neck Malignancy -- Intensity-Modulated Radiation Therapy in the Management of Head and Neck Cancer -- Altered Fractionation -- The Role of Tumor Hypoxia in Head and Neck Cancer Radiotherapy -- Induction Chemotherapy in Head and Neck Cancer -- The Evolution of Induction Chemotherapy in Locally Advanced Squamous Cell Cancer of the Head and Neck -- Concurrent Chemoradiotherapy -- Postoperative Treatment of Locally Advanced Head and Neck Cancers -- Multimodality Management of Nasopharyngeal Carcinoma -- Strategies for Protecting Normal Tissue in the Treatment of Head and Neck Cancer -- Targeted Therapies in Head and Neck Cancer -- Gene Therapy for Patients With Head and Neck Cancer -- Chemoprevention in Head and Neck Cancer -- Quality of Life Outcomes in Head and Neck Cancer -- Palliation of Head and Neck Cancer.
Keywords: Oncology .; Oncology